Facile synthesis and fundamental properties of an N-methylguanidine-bridged nucleic acid (GuNA[NMe]). Issue 35 (30th August 2018) - Horie, Naohiro; Kumagai, Shinji; Kotobuki, Yutaro; Yamaguchi, Takao; Obika, Satoshi
Abstract : The GuNA[NMe]-modified oligonucleotides exhibited excellent duplex-forming ability towards the complementary single-stranded DNA and RNA, and showed robust enzymatic stability. Abstract : An N -methylguanidine-bridged nucleic acid (GuNA[NMe]), a guanidine-bridged nucleic acid (GuNA) bearing a methyl substituent at the bridge, was successfully synthesised and incorporated into oligonucleotides. By employing an acetyl protecting group, GuNA[NMe]-modified oligonucleotides bearing acid-sensitive purine nucleobases were successfully prepared. The obtained GuNA[NMe]-modified oligonucleotides exhibit excellent binding affinity towards the complementary single-stranded RNA and DNA. Furthermore, even a single GuNA[NMe] modification provides robust enzymatic stability, similar to that achieved by the well-established phosphorothioate backbone modification. These data indicate that such a GuNA[NMe] represents a valuable modification for the development of therapeutic oligonucleotides.